1956
DOI: 10.1037/h0047282
|View full text |Cite
|
Sign up to set email alerts
|

The effects of repeated doses of total-body X radiation on motivation and learning in rhesus monkeys.

Abstract: "Compared with the performance of 11 control animals, the [12] radiated monkeys showed no deficits on complex learning tasks but showed significant decreases in weight gain, appetite and locomotor activity, with these decreases being roughly proportional to the cumulative dosage absorbed. Radiated monkeys were superior in performance on two of the learning tests during the later stages of the investigation. This superiority may have been the result of decreased activity and distractibility . . . . These data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1965
1965
1983
1983

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Spact and Harlow (1943) and Harlow and Moon (1956) trained their rhesus monkeys in the WGTA to choose an odd object on one color of the tray and to choose a nonodd object on another color of We tray. They demonstrated that rhesus monkeys are able to master this higher-order conditional discrimination task named "oddity-nonoddity" problem.…”
Section: Discussionmentioning
confidence: 99%
“…Spact and Harlow (1943) and Harlow and Moon (1956) trained their rhesus monkeys in the WGTA to choose an odd object on one color of the tray and to choose a nonodd object on another color of We tray. They demonstrated that rhesus monkeys are able to master this higher-order conditional discrimination task named "oddity-nonoddity" problem.…”
Section: Discussionmentioning
confidence: 99%
“…Whole body irradiated rhesus monkeys showed no significant difference from controls in their ability to learn to discriminate by observing mirrored cues (Brown et al, 1965). Harlow and Moon (1956) showed a relative increase in the learning of oddity set problems although the difference between experimental and control subjects appears to be a result of some sort of interference in the control animals on later problems (Overall et al, 1960). McDowell (1960) felt Harlow and Moon's results could be explained by an increasing boredom in the controls and decreased distractibility in the irradiated animals.…”
Section: Operant Conditioningmentioning
confidence: 73%
“…Monkeys receiving lethel doses of x-rays to parts of the head showed no variation in performance on problems of delayed response, discrimination, and oddity until motor disturbance preceding death occurred (Davis'and McDowell, 1962). Performances on problems of delayed response, discrimination and oddity did not vary after whole-body irradiation (Davis, 1963;Davis et al, 1956;Davis et al, 1958;Harlow and Moon, 1956;Riopelle et al, 1956). The effects of previous gamma plus neutron irradiation on rhesus monkeys was not statistically evident in tests of ambivalent cue, delayed-response performance (McDowell and Brown, 1963h).…”
Section: Operant Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…There are at least two previous experiments which provided conclusive evidence for the use of conceptual conditionals by monkeys, one from this laboratory using Saimiri sciureus (Thomas & Kerr, 1976) and one by RiopeIle and Copelan (1954) using Macaca mulatta. Except for the obscureness of the first-trial performances on three-trial presentations of new oddity problems, the experiment by Harlow and Moon (1956) might also be regarded as having provided conclusive evidence for conceptual conditional behavior by Macaca mulatta.…”
Section: Discussionmentioning
confidence: 99%